Successful strategies in drama translation: Yasmina Reza’s “Art” - Mateo, Marta (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractYasmina Reza’s “Art” has been widely acclaimed ever since it opened in Paris in 1994: the different productions which have followed the French original in more than 40 countries have enjoyed equal success. This success, both among audiences and critics, may be attributed to the play’s universal themes, to the tone and richness of its dialogue and to the good acting most productions have displayed. But the fact that the play has been appreciated in so many different countries and languages inevitably implies that translation is also at the centre of its success. This paper analyses two translations of “Art” – Christopher Hampton’s English text and Josep M. Flotats’s version into Spanish –, which, despite having a similar aim, i.e., making the play function on stage, have followed different translation strategies to make it work in their different target contexts.